Evaluating the Implementation and Effectiveness of Inquiry-based Learning to Teaching Paper-based GIS in Secondary Schools - Thulasizwe Fredrick Mkhize; Zanele Heavy-Girl Dube-Xaba; Thabile Aretha Zondi (E-Journal of Humanities, Arts and Social Sciences, 2024)
This study evaluated the implementation and effectiveness of inquiry-based learning in teaching paper-based geographic information systems (PBGIS) in South African secondary schools. PBGIS refers to teaching GIS through maps without using digital applications such as Quantum GIS and ArcGIS. The Department of Basic Education (DBE) has not provided geography teachers with clear guidelines for teaching PBGIS. Although DBE has provided geography teachers with sufficient PBGIS content, PBGIS pedagogical approaches are still fragmented. National Senior Certificate diagnostic reports indicate poor performance of learners on questions related to GIS in the examinations. The Technological Pedagogical Content Knowledge is the conceptual framework used to understand the implementation and effectiveness of Inquiry-based Learning (IBL) in teaching PBGIS in secondary schools. This interpretive paradigm study underpinned the qualitative research design. The findings show that geography teachers implement IBL to engage learners in PBGIS research projects and mapwork activities that use scenarios to solve problems. Teachers believe using IBL is effective because it assists learners in becoming critical thinkers and developing skills to question their curiosity to construct knowledge through research projects. The study recommends that geography teachers use IBL to teach PBGIS in ways that stimulate learners’ critical thinking and help them learn to collaborate with others during the inquiry process. The study’s contribution may assist the DBE, teachers, learners, lecturers, and students with insights toward understanding the implementation and effectiveness of IBL in teaching PBGIS in secondary schools.